Efektivitas Program Pelatihan Berbasis Kompetensi dalam Meningkatkan Kualitas Tenaga Kerja di UPTD BLK Kabupaten Kotawaringin Timur - Saffa Indah Salsabila; Diana Hertati (PERSPEKTIF, 2022)
The local government of East Kotawaringin Regency through the UPTD BLK which is located under the Manpower and Transmigration Service organizes a program in the form of competency-based training as an effort to overcome the problem of the low quality of the workforce. East Kotawaringin Regency as an area dominated by individuals with low educational backgrounds, in the process of implementing training to improve the quality of its workforce has several problems that accompany it. This study aims to describe the effectiveness of competency-based training programs in improving the quality of the workforce in the UPTD BLK of East Kotawaringin Regency which was analyzed using the training effectiveness measure from Henry Simamora. The type of research used is the type of qualitative research with data collection techniques in the form of observation, interviews, and documentation. The results showed that; 1) the feeling of the training participants towards the training subjects was not entirely good because the availability of facilities at the UPTD BLK in East Kotawaringin Regency was considered inadequate; 2) the learning provided in competency-based training at the UPTD BLK of East Kotawaringin Regency has been able to make the trainees master the concepts and knowledge acquired during the training process; 3) the behavior of the trainees has changed in attitudes, knowledge and skills after the training; 4) the pass rate of participants with certificates at the UPTD BLK of East Kotawaringin Regency is quite good, reaching 92% of participants.